Simulation of LMS algorithm for active noise cancellation: article / Ahmad Khairul Hafiz Abdullah - Abdullah, Ahmad Khairul Hafiz (2012)
This paper presents the simulation of (least mean square) LMS method using Matlab to adjust the coefficient of the adaptive filter in order to match the desired response with mp3 music data as external source. Xilinx ISE is employed to design the adaptive filter by using Verilog programming.